2000
DOI: 10.1054/bjoc.1999.1130
|View full text |Cite
|
Sign up to set email alerts
|

Expression of αvβ6integrin in oral leukoplakia

Abstract: SummaryThe distribution of α v β 6 integrin was examined in oral leukoplakia, lichen planus and squamous cell carcinomas using immunohistochemistry. Controls included oral mucosal wounds, chronically inflamed and normal oral mucosa. Integrins β 1 , β 3 , β 4 , β 5 , fibronectin and tenascin were also studied. The integrin α v β 6 was highly expressed throughout the whole lesion of 90% of the squamous cell carcinomas but was not present in any of the normal specimens. α v β 6 integrin was also expressed in 41% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
57
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 45 publications
1
57
1
2
Order By: Relevance
“…De novo expression of avb6 is seen in a number of epithelial malignancies, particularly oral squamous cell carcinoma (SCC) (Breuss et al, 1995;Jones et al, 1997;Hamidi et al, 2000;Ahmed et al, 2002). Expression of this integrin is often higher at the invasive front, supporting the contention that avb6 is capable of playing an active role in tumour progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo expression of avb6 is seen in a number of epithelial malignancies, particularly oral squamous cell carcinoma (SCC) (Breuss et al, 1995;Jones et al, 1997;Hamidi et al, 2000;Ahmed et al, 2002). Expression of this integrin is often higher at the invasive front, supporting the contention that avb6 is capable of playing an active role in tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of avb6 is not detectable on keratinocytes in adult oral epithelium or epidermis. However, several studies have found high expression of avb6 in oral squamous cell (and other carcinomas), suggesting that this integrin may play a role in tumour progression (Breuss et al, 1995;Jones et al, 1997;Arihiro et al, 2000;Hamidi et al, 2000;Ahmed et al, 2002).…”
mentioning
confidence: 99%
“…8,98-100 However, both a v b 6 and a v b 5 are upregulated during wound healing, 8,[98][99][100] where each may bind to several ECM ligands through the arginine-glycine-aspartate (RGD) motif (e.g., fibronectin, tenascin, vitronectin). 3,40 Given the diversity of ligands that a v integrins can bind, their upregulation in wound epidermis may be important for modulating keratinocyte motility over the complex matrix of the wound bed.…”
mentioning
confidence: 99%
“…[2][3][4] Within the ␣v subfamily, the ␣v␤6 integrin is either not expressed or expressed at low levels in normal adult epithelia; however, it becomes highly expressed during tumourigenesis. 5,6 For example, induction of ␣v␤6 expression in oral leukoplakia appears to be a necessary prerequisite for progression to squamous cell cancer 7 and de novo expression of ␣v␤6 has been observed in oral squamous and colon cancers. 8,9 In lung cancer, approximately 50% of tumours exhibit upregulation of the ␣v␤6 subunit, 10 and in breast cancer ␣v␤6 expression has recently been linked to more advanced tumours.…”
mentioning
confidence: 99%